Reflection-based community learning design for sustainable ecotourism: Integration of design thinking and indigenous climate education in digital-social agrotourism - Wulandari, Dwi; Yunikawati, Nur Anita; Fajarianto, Otto; Prasetyo, Abdul Rahman; Gunawan, Ari (International Journal of Innovative Research and Scientific Studies, 2025)
The development of sustainable ecotourism that integrates design thinking and indigenous Climate education in Digital-Social Agrotourism is supported by the important role of reflection-based community learning design. The community in this study is a reflective actor who actively designs and manages the adaptive and participatory learning process. Key elements in learning design implemented through cross-stakeholder collaboration, including learning facilitators, local governments, creative industry players, and indigenous peoples, are case studies to be analyzed. Thematic analysis focusing on in-situ and post-implementation reflection identifies challenges and opportunities in the community learning process, such as integrating digital technologies, preserving local wisdom, and adaptation to climate change. The development of social innovation capacity and ecotourism management that is ecologically and socially sustainable will also be supported by community reflection. The results of this study highlight the importance of facilitator capacity building and ongoing collaboration in supporting a responsive and inclusive community learning ecosystem. The implications of this research can guide the development of community learning models and ecotourism support policies based on digital technology and local wisdom in the future.